Manajemen Sumber Daya Manusia Pustakawan Di Dinas Perpustakaan Dan Arsip Provinsi Sumatera Utara (International Forum of Researchers and Lecturers, 2024)
This research discusses the human resource management of librarians at the North Sumatra Provincial Library and Archives Office. The purpose of this research is to know the management and obstacles in human resource development at the Library and Archives Office of North Sumatra Province. This type of research is qualitative research with a descriptive approach, namely describing and describing the data and then analyzing the data obtained from the field so that the data and information obtained are explained without any engineering. Data collection techniques in this study are through observation, interviews, and documentation. The informants in this study amounted to 4 people which consisted of librarian functional HR empowerment section, library material development and processing section, expert level librarians and skilled or supervisory level librarians. The results showed that the recruitment and selection process of human resources in the library of the North Sumatra Provincial Library and Archives Office was regulated by the BKD (Regional Personnel Agency) and the one who determined employee acceptance was the BKN (State Personnel Agency), the suitability of organizing management in the placement of each employee according to their expertise, There are efforts to increase the participation of all group members in cooperation in order to realize the objectives of a plan through family gathering activities and rewards in the form of TPP (Additional Employee Income) and activities carried out in accordance with existing plans, namely the attitude and discipline of librarians who are in accordance with the rules that apply in the library of the library and archives office of the province of North Sumatra and there are several corrections such as S. O.P. librarian performance. O.P librarian performance that has not been implemented but replaced with S.O.P excellent service only. The obstacles in fostering librarians are the less communicative communication process and the limited budget.